Kerjasama Pemerintah dan Swasta Dalam Pengelolaan Limbah Medis Covid-19 di Kota Madiun - Arimurti Kriswibowo; Amelia Wahyuningtiyas; Nur Wandira Kusmayadi; Khusnul Prasetyo (Public Inspiration : Jurnal Administrasi Publik, 2021)
The increasing spread of disease caused by the SARS-CoV-2 virus in Madiun City is also in line with the increase in the amount of medical waste generated from handling COVID-19 both in Hajj Dormitories, Emergency Medical Train (EMT) and dr. Soedono Kota Madiun is categorized as B3 waste. To solve the problem of medical waste COVID-19, the Madiun City Health, Population Control, and Family Planning Agency (Dinkes-PPKB) collaborates with PT. Triata Mulia Indonesia in managing COVID-19 medical waste, considering that B3 waste management can only be carried out by the government, third parties, and hospitals that have incinerators. This study aims to describe the partnership between DinKes-PPKB Madiun City and PT. Triata Mulia Indonesia in managing COVID-19 medical waste based on the hollow state theory, as well as examining the benefits and obstacles faced in its implementation. This research uses descriptive qualitative research methods, with data collection techniques in the form of interviews, observation, and documentation. The results of this study indicate that the collaboration between the Health Office-PPKB Madiun City and PT. Triata Mulia Utama in terms of managing COVID-19 medical waste has been running effectively because both parties have carried out their respective roles.